Infrahepatic inferior caval and azygos vein formation in mammals with different degrees of mesonephric development. Issue 3 (11th December 2015) - Hikspoors, Jill P. J. M.; Mekonen, Hayelom K.; Mommen, Greet M. C.; Cornillie, Pieter; Köhler, S. Eleonore; Lamers, Wouter H.
Abstract: Controversies regarding the development of the mammalian infrahepatic inferior caval and azygos veins arise from using topography rather than developmental origin as criteria to define venous systems and centre on veins that surround the mesonephros. We compared caudal‐vein development in man with that in rodents and pigs (rudimentary and extensive mesonephric development, respectively), and usedAmira 3D reconstruction andCinema 4D‐remodelling software for visualisation. The caudal cardinal veins (CCVs) were the only contributors to the inferior caval (IVC) and azygos veins. Development was comparable if temporary vessels that drain the large porcine mesonephros were taken into account. The topography of the CCVs changed concomitant with expansion of adjacent organs (lungs, meso‐ and metanephroi). The iliac veins arose by gradual extension of the CCVs into the caudal body region. Irrespective of the degree of mesonephric development, the infrarenal part of the IVC developed from the right CCV and the renal part from vascular sprouts of the CCVs in the mesonephros that formed 'subcardinal' veins. The azygos venous system developed from the cranial remnants of the CCVs. Temporary venous collaterals in and around the thoracic sympathetic trunk were interpreted as 'footprints' of the dorsolateral‐to‐ventromedial change in the local course of the intersegmental and caudal cardinal veins relative to the sympathetic trunk. Interspecies differences in timing of the same events in IVC and azygos‐vein development appear to allow for proper joining of conduits for caudal venous return, whereas local changes in topography appear to accommodate efficient venous perfusion. These findings demonstrate that new systems, such as the 'supracardinal' veins, are not necessary to account for changes in the course of the main venous conduits of the embryo.